The modulatory effects of rostral ventromedial medulla on air-puff evoked microarousals in rats - Foo, H. (2010)
This study tested whether the duration of microarousals from sleep evoked by innocuous air-puff is affected by intra-RVM administration of neurotensin and bicuculline, pharmacological manipulations that affect ON and OFF cell activity. Air-puff evoked microarousal duration was unaffected by 0.05 ng neurotensin, but decreased by 502 ng neurotensin, and 5 and 50 ng bicuculline. These results suggest a putative role for OFF cells in protecting sleep from interruption by non-noxious stimuli.